Prevention of orofacial clefts caused by smoking: implications of the Surgeon General’s Report - Honein, Margaret A. (Birth Defects Res A Clin Mol Teratol, 2014)
INTRODUCTION: According to the 2014 Surgeon General’s Report, smoking in early pregnancy can cause orofacial clefts. We sought to examine the implications of this causal link for the potential prevention of orofacial clefts in the United States. METHODS: Using published data on the strength of the association between orofacial clefts and smoking in early pregnancy and the prevalence of smoking at the start of pregnancy, we estimated the attributable fraction for smoking as a cause of orofacial clefts. We then used the prevalence of orofacial clefts in the United States to estimate the number of orofacial clefts that could be prevented in the United States each year by eliminating exposure to smoking during early pregnancy. We also estimated the financial impact of preventing orofacial clefts caused by maternal smoking based on a published estimate of attributable healthcare costs through age 10 for orofacial clefts. RESULTS: The estimated attributable fraction of orofacial clefts caused by smoking in early pregnancy was 6.1% (95% uncertainty interval 4.4%, 7.7%). Complete elimination of smoking in early pregnancy could prevent orofacial clefts in approximately 430 infants per year in the United States, and could save an estimated $40.4 million in discounted healthcare costs through age 10 for each birth cohort. CONCLUSION: Understanding the magnitude of the preventable burden of orofacial clefts related to maternal smoking could help focus smoking cessation efforts on women who might become pregnant.